2020
DOI: 10.1111/1754-9485.13071
|View full text |Cite
|
Sign up to set email alerts
|

Gastrografin can be detected in ex vivo biological specimens by dual‐energy CT scanning

Abstract: Background: Dual-energy CT is able to distinguish between materials based on differences in X-ray absorption at different X-ray beam energies. The strong k-edge photoelectric effect of materials with a high atomic number makes this modality ideal for identifying iodine-containing compounds. We aim to evaluate dual-energy CT for the detection of Gastrografin (GG) (diatrizoate, Bayer PLC, Reading, UK) enteric contrast medium and validate the conditions for the measurement in ex vivo samples. Methods: Dual-energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The upper limit of the true negative levels of GG measured in drain fluid by DECT was derived by calculating the mean (+3 standard deviation (SD)) iodine density (mg/mL) in GG negative samples. We have established measurements of iodine density above 1.2 mg/mL to represent a positive result for the presence of GG in a solution measured by DECT [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The upper limit of the true negative levels of GG measured in drain fluid by DECT was derived by calculating the mean (+3 standard deviation (SD)) iodine density (mg/mL) in GG negative samples. We have established measurements of iodine density above 1.2 mg/mL to represent a positive result for the presence of GG in a solution measured by DECT [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…We have established measurements of iodine density above 1.2 mg/ml to represent a positive result for the presence of GG in a solution measured by DECT. [4]…”
Section: A R T I C L Ementioning
confidence: 99%
See 1 more Smart Citation
“…The measurement of drain fluid amylase or drain fluid Gastrografin may achieve this end and there is emerging evidence of their utility as sensitive BMs for early AL. [17][18][19][20][21] Patients without a TDI are likely to present more dramatically and earlier in their post-operative recovery.…”
Section: Does An Ileostomy Cover the Surgeon Or The Anastomosis?mentioning
confidence: 99%
“…Two assessed drain fluid gastrografin as a BM, in phase 1 and 2 studies. The authors defined a threshold level of 0.2% gastrografin (1.23 mg/ml iodine) as measured by dual energy computerised tomography [34] and two assessed drain fluid amylase and lipase in ileal patients and those undergoing a low anterior resection. A pilot study of 13 ileal pouch patients suggested that drain fluid amylase might be a sensitive BM of AL [35].…”
Section: Registered Trials Of Drain Fluid Biomarkersmentioning
confidence: 99%